Seed-coat thickness explains contrasting germination responses to smoke and heat in Leucadendron - Lamont, Byron; Gomez Barreiro, Pablo; Newton, Rosemary J (CAMBRIDGE UNIV PRESS, 2022)
Fire stimulates the germination of most seeds in fire-prone vegetation. Fruits of Leucadendron (Proteaceae) are winged achenes or nutlets that correlate with their requirements for smoke and/or heat in promoting germination. We describe five possible smoke–heat dormancy-release/germination syndromes among plants, of which Leucadendron displays three (no response, smoke only, smoke and heat). As seed-coat thickness varies with seed-storage location (plant or soil) and morphology (winged or wingless), we tested its possible role in water uptake and germination. Species with winged seeds achieved 100% germination in the absence of smoke/heat, seed coats were an order of magnitude thinner, and their permeability greatly exceeded that of nutlets. As seed-coat thickness increased (1) imbibitional water uptake declined at a decreasing rate, and (2) the response to smoke, and to a lesser extent heat, increased linearly to reach levels of germination approaching those of winged seeds. For species responsive to smoke and heat, there was no additive effect when applied together, suggesting that they may have promoted the same physiological process. We conclude that seed-coat thickness holds the key to germination requirements in this genus, independent of seed-storage location or morphology. By what mechanisms (1) the smoke response is greater the thicker the seed coat and (2) smoke chemicals might increase water permeability to explain the non-additive effect of smoke and heat, warrant further investigation.